Genetic evidence for a functional association between Parkinson’s disease proteins leucine-rich repeat kinase 2 and α-synuclein during axonal transport - Chakraborty, Piyali; Bajgain, Pratima; Huang, Jing; Islam, Rakibul; Banerjee, Rupkatha; Gunawardena, Shermali (Frontiers in Molecular Neuroscience, 2026)
Mutations in α-synuclein (α-syn) and LRRK2 cause familial Parkinson’s disease (fPD), yet how these proteins functionally interact remain ambiguous. We previously showed that α-syn undergoes bi-directional transport within axons and influences mitochondrial health, while other studies suggested that LRRK2-G2019S disrupts the axonal transport of autophagic vesicles and mitochondria. Here we tested the hypothesis that α-syn and LRRK2 are functionally linked during axonal transport. Expression of human LRRK2-WT in Drosophila larval nerves caused modest CSP-containing axonal blockages whereas no defects were seen in LRRK2 loss of function mutants in contrast to other proteins directly involved in axonal transport. Surprisingly, fPD mutations in the GTPase (LRRK2-Y1699C) and WD40 (LRRK2-G2385R) domains suppressed axonal blocks compared to LRRK2-WT, while kinase-domain mutant G2019S enhanced them. Reducing kinesin-1 had no effect with LRRK2-WT, but increased axonal transport defects with LRRK2-G2385R suggesting a functional interaction between the LRRK2 WD40 domain and the anterograde transport machinery. Further, co-expression of α-syn with either the GTPase domain or WD40 domain LRRK2 fPD mutants significantly suppressed α-syn-mediated axonal transport defects, decreased stalled α-syn-vesicles, but did not alter α-syn-mediated neuronal cell death. Taken together, these results suggest that while LRRK2 itself may not play an independent role in axonal transport, its GTPase and WD40 domains likely associate functionally with α-syn during transport within axons.